2002
DOI: 10.1128/jb.184.9.2473-2480.2002
|View full text |Cite
|
Sign up to set email alerts
|

Firm but Slippery Attachment of Deinococcus geothermalis

Abstract: Bacterial biofilms impair the operation of many industrial processes. Deinococcus geothermalis is efficient primary biofilm former in paper machine water, functioning as an adhesion platform for secondary biofilm bacteria. It produces thick biofilms on various abiotic surfaces, but the mechanism of attachment is not known. High-resolution field-emission scanning electron microscopy and atomic force microscopy (AFM) showed peritrichous adhesion threads mediating the attachment of D. geothermalis E50051 to stain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
59
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 32 publications
(73 reference statements)
1
59
0
Order By: Relevance
“…3) and, therefore, the images indicate that the surface appendages of live cells are the location of glycoconjugates both in individual surface-adhered cells and inside biofilm colonies. Previous studies (18,29) showed that an extensive slime matrix is absent in D. geothermalis biofilms, which discards the possibility that lectins may bind matrix exopolysaccharides. According to the manufacturer, Amaranthus caudatus lectin has specificity for oligosaccharides containing galactosyl Gal␤(1,3)GalNAc ␣-units.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…3) and, therefore, the images indicate that the surface appendages of live cells are the location of glycoconjugates both in individual surface-adhered cells and inside biofilm colonies. Previous studies (18,29) showed that an extensive slime matrix is absent in D. geothermalis biofilms, which discards the possibility that lectins may bind matrix exopolysaccharides. According to the manufacturer, Amaranthus caudatus lectin has specificity for oligosaccharides containing galactosyl Gal␤(1,3)GalNAc ␣-units.…”
Section: Discussionmentioning
confidence: 99%
“…Although Deinococcaceae are considered nonmotile, a pre- vious study described the ability of D. geothermalis E50051 to slide away from mechanical stress (18). Similarly, adhesion pili from uropathogenic Escherichia coli are capable of a structural transition which allows the pilus to unravel and extend plastically (3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Drying is expected to significantly change the strength and overall character of a biofilm; therefore, measurements made on dry biofilm must be interpreted and applied carefully. A few AFM studies have investigated biofilm properties, such as interaction and attachment to surfaces under aqueous conditions (5,21). Yet, there is a real need to expand this work to study additional properties of whole biofilms under aqueous conditions.…”
mentioning
confidence: 99%